Informality in International Judicial Appointments : A Relational Approach to Sub-Regional Courts - Kisakye, Diana (Cluster Conference "Africa*n Relations : Modalities Reflected, 2021)
Recent scholarship on judicial politics has highlighted the relevance of informal judicial networks and relations as a prerequisite for protecting judicial autonomy and independence. Relational dynamics unravel the concealed but salient ties and entanglements that inform, steer and shape the nature of judicial-executive relations. Our paper keeps in conversation with this strand of research and asks whether and how informalities feature in and influence judicial appointments to African Regional Economic Community (REC) courts. To conceptualise the governance and patterns of judicial appointments, we use an originally compiled dataset comprising all 105 judges who serve(d) on the four operational African Union sanctioned REC courts. We also draw on interview material to divulge the informal dimension of the appointment processes whilst accounting for their variations across regime types. We show that the formal selection rules are particularly thin, leaving much leverage to informal processes at various levels of governance. We, therefore, argue that appointments tell us at least part of the informal selection story from two angles: the merits, ties and efforts that enhance the chances of individuals getting selected, as well as the appointers’ strategies and criteria for selecting specific individuals from a larger pool of candidates.
Keywords: Informality; International judicial appointments; Relational approach